High modulated soliton power propagation interaction with optical fiber and optical wireless communication channels - Mahmoud M. A. Eid; Ashraf S. Seliem; Ahmed Nabih Zaki Rashed; Abd El-Naser A. Mohammed; Mohamed Yassin Ali; Shaimaa S. Abaza (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This paper has presented high modulated soliton power transmission interaction with optical fiber and optical wireless communication channels at flow rate of 40 Gbps and 20 km link range. The proposed modulation schemes are continuous phase frequency shift keying (CPFSK), Quadrature amplitude modulation (QAM), differential phase shift keying (DPSK), frequency shift keying (FSK), pulse amplitude modulation (PAM), minimum shift keying (MSK), and optical quadrature phase shift keying (OQPSK). CPFSK has presented better performance than other proposed modulation schemes for both optical fiber and optical wireless communication channels. The enhancement of optical signal/noise ratio at fiber/wireless channel, received electrical power and signal/noise ratio at optical receiver with increase of bits per symbol for different proposed modulation schemes except for CPFSK scheme. Therefore it is evident that CPFSK modulation scheme is more efficient and better performance than other modulation schemes for different communication channels. The obtained results are simulated with optisystem program version 13.